“Putting it all together”: Highlighting the global approach to chronic total occlusion revascularization - Mohamad Lazkani; Divya Ratan Verma; Michael Morris; Ashish Pershad (Indian Heart Journal, 2016)
Preprocedural planning and advanced imaging is vital to achieve a consistent and high level of success for complex coronary chronic total occlusion (CTO) revascularization. Various practice patterns exist around the world when performing coronary artery CTO revascularization. This case report highlights a fusion of global practices in CTO intervention and integration of advanced imaging to achieve successful revascularization.